Autoantibodies in systemic sclerosis: From disease bystanders to pathogenic players - Aurélien Chepy; Aurore Collet; David Launay; Sylvain Dubucquoi; Vincent Sobanski (Journal of Translational Autoimmunity)
Autoantibodies (Aab) are recognized as key indicators in the diagnosis, classification, and monitoring of systemic autoimmune diseases (AID). Recent studies have expanded knowledge through the discovery of new antigenic targets, advanced methods for measuring Aab levels, and understanding their possible pathogenic roles in AID. This narrative review uses systemic sclerosis (SSc) as an example to highlight the importance of Aab associated with HEp-2 immunofluorescence assay positivity (traditionally referred as antinuclear antibodies [ANA]), exploring recent developments in the field. Firstly, we outline the various types of ANA found in SSc and their links with specific disease features. Newly discovered antibodies shed light on SSc cases where Aab had previously gone unidentified. Secondly, we emphasize the necessity for novel quantitative techniques to track Aab levels over time by gathering data regarding the timing of Aab occurrence relative to SSc symptoms and the relationships between Aab concentrations and disease severity. Finally, we discuss the experimental findings suggesting a potential direct role of Aab in the development of SSc. The advancements surrounding Aab provide insights into new disease mechanisms and may lead to innovative diagnostic and treatment approaches.